1984
DOI: 10.1002/mrd.1120090204
|View full text |Cite
|
Sign up to set email alerts
|

Culture of mouse preimplantation embryos as a quality control assay for human in vitro fertilization

Abstract: Techniques for culturing preimplantation mouse embryos from the two-cell stage to blastocyst are described, and the importance of this system to quality control assay the media and supplements used in human in vitro fertilization (IVF) procedures is discussed. Embryos from B6CBAF, mice were cultured in a commonly used mouse culture medium, modified Krebs-Ringer-bicarbonate (Krebs'), or in a commonly used human culture medium, Ham's FIO nutrient mixture supplemented with human fetal cord serum (FCS), and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Several studies (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(16)(17)(18) have shown that successful culture of human embryos in an IVF program requires good laboratory procedures and selection of nonembryo-toxic equipment and culture products. Different embryonic stages show different sensitivities to toxic effects, and this is why we have used both (ZPþ) and (ZP-) zygotes and not only fresh but also frozen/thawed embryos (1,4,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(16)(17)(18) have shown that successful culture of human embryos in an IVF program requires good laboratory procedures and selection of nonembryo-toxic equipment and culture products. Different embryonic stages show different sensitivities to toxic effects, and this is why we have used both (ZPþ) and (ZP-) zygotes and not only fresh but also frozen/thawed embryos (1,4,10).…”
Section: Discussionmentioning
confidence: 99%
“…Here we cultured 2-cell embryos to the blastocyst stage; the observed development and proportions of blastocysts reaching expanded and hatching stages were similar under culture conditions with and without protein supplementation. We have used this system for embryo toxicity and quality control in our IVF program for several years [19]. We pooled samples and used concentration methods in order to increase protein abundances, and embryos were cultured without change in media for the 3-day period in an effort to accumulate secretory products.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an alternative model like the rabbit (Kuehl et al 1986) may be useful Details for establishing mouse embryo cultures for quality control purposes appear elsewhere (Hogan et al, 1986;Monk, 1987;Gerrity, 1988). For human in vitro fertilization programs, 1-to 4-cell mouse embryos are used, and development is monitored to the hatched b astocyst stage over a 3-to 5-day period (Ackerman et al, 1984;Trouson andConto 1984-Heming et al, 1987). Cryopreserved 2-cell mouse embryos can be purchased from commercial sources for quahty control assessments (Leibo, 1990).…”
Section: Guidelines For Quality Controlmentioning
confidence: 99%